Metabolic reprogramming of hypoxic tumor-associated macrophages through CSF-1R targeting favors treatment efficiency in colorectal cancers - Arnaud Millet; Khaldoun Gharzeddine; Cristina Gonzalez Prieto; Marie Malier; Clara Hennot; Renata Grespan; Yoshiki Yamaryo-Botté; Cyrille Y Botté; Fabienne Thomas; Marie-Hélène Laverriere; Edouard Girard; Gael Roth (Journal for ImmunoTherapy of Cancer)
Background Tumor-associated macrophages participate in the complex network of support that favors tumor growth. Among the various strategies that have been developed to target these cells, the blockade of the colony-stimulating factor 1 receptor (CSF-1R) receptor is one of the most promising ones. Here, we characterize the resulting state of human macrophages exposed to a CSF-1R kinase inhibitor.Methods Using RNA sequencing and metabolomics approach, we characterize the reprogramming of human monocyte-derived macrophages under CSF-1R targeting.Results We find that CSF-1R receptor inhibition in human macrophages is able to impair cholesterol synthesis, fatty acid metabolism and hypoxia-driven expression of dihydropyrimidine dehydrogenase, an enzyme responsible for the 5-fluorouracil macrophage-mediated chemoresistance. We show that this inhibition of the CSF-1R receptor leads to a downregulation of the expression of sterol regulatory element-binding protein 2, a transcription factor that controls cholesterol and fatty acid synthesis. We also show that the inhibition of extracellular signal-regulated kinase 1/2 phosphorylation resulting from targeting the CSF-1R receptor destabilizes the expression of hypoxic induced factor 2 alpha in hypoxia resulting in the downregulation of dihydropyrimidine dehydrogenase expression restoring the sensitivity to 5-fluorouracil in colorectal cancer.Conclusions These results reveal the unexpected metabolic rewiring resulting from the CSF-1R receptor targeting of human macrophages and its potential to reverse macrophage-mediated chemoresistance in colorectal tumors.